Penggunaan Eceng Gondok (Eichhorina Crassipes) Sebagai Bahan Bakar Alternatif Biobriket di Danau Galela - Kusman, Muhammad Reza; Faruk, Fitriyanti; Sibua, Sakila (Jurnal Serambi Engineering, 2024)
The use of water hyacinth as an alternative fuel in Lake Galera is one of the solutions to the problem of water hyacinth invasion, which is currently spiralling out of control. This problem should be taken seriously as it affects the economic life of communities that depend on fishing and fish farming. Solutions to the problem of water hyacinth in Lake Galera have been sought for a long time, but the results have not been positive, as water hyacinth has become a natural waste with no benefit. In this study, we will try to use water hyacinth waste as one of the raw materials for the production of briquettes, so that we can benefit from the water hyacinth resource, which is one of the causes of water problems in Lake Galela. To be used in bio-briquettes, charcoal is first processed into charcoal, then the charcoal is crushed, mixed and formed into a cylindrical shape. This briquette material is later analysed and tested for its physical and chemical properties, resulting in a briquette mixture that can be used as an alternative fuel. The use of water hyacinth as bio-briquettes is likely to be a solution that can reduce the amount of water hyacinth in Lake Galela.